2014
DOI: 10.1590/s0100-06832014000300024
|View full text |Cite
|
Sign up to set email alerts
|

Effect of management systems and cover crops on organic matter dynamics of soil under vegetables

Abstract: SUMMARYVegetable production in conservation tillage has increased in Brazil, with positive effects on the soil quality. Since management systems alter the quantity and quality of organic matter, this study evaluated the influence of different management systems and cover crops on the organic matter dynamics of a dystrophic Red Latosol under vegetables. The treatments consisted of the combination of three soil tillage systems: no-tillage (NT), reduced tillage (RT) and conventional tillage (CT) and of two cover … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0
7

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 37 publications
1
11
0
7
Order By: Relevance
“…2016 DOI: 10.1590/S0100-204X2016000900050 2013), bem como melhorias dos atributos físicos e químicos Siqueira Neto et al, 2010;Guareschi et al, 2012aGuareschi et al, , 2013Beutler et al, 2015) e biológicos (Leite et al, 2010;Pereira et al, 2013). No entanto, ainda são poucos os estudos que avaliam a dinâmica da matéria orgânica e de suas frações, ou os benefícios destas, em solos sob sistemas plantio direto de hortaliças (SPDH) no cerrado (Souza et al, 2014a(Souza et al, , 2014b.…”
Section: Introductionunclassified
See 1 more Smart Citation
“…2016 DOI: 10.1590/S0100-204X2016000900050 2013), bem como melhorias dos atributos físicos e químicos Siqueira Neto et al, 2010;Guareschi et al, 2012aGuareschi et al, , 2013Beutler et al, 2015) e biológicos (Leite et al, 2010;Pereira et al, 2013). No entanto, ainda são poucos os estudos que avaliam a dinâmica da matéria orgânica e de suas frações, ou os benefícios destas, em solos sob sistemas plantio direto de hortaliças (SPDH) no cerrado (Souza et al, 2014a(Souza et al, , 2014b.…”
Section: Introductionunclassified
“…De maneira similar, Souza et al (2014a) verificaram que a adoção de SPD no cultivo de repolho reduziu em 90% as taxas de perda de água, em comparação ao plantio convencional. Em outro estudo, Souza et al (2014b) relatam que o SPDH favorece o aumento do C orgânico total (COT) e das frações mais lábeis e oxidáveis da matéria orgânica, principalmente na camada superficial do solo, em comparação ao plantio convencional (SPC); no entanto, segundo os autores, o SPDH somente promoveu o aumento nos teores de humina, na área de SPD com hortaliças. No Estado do Rio de Janeiro, Loss et al (2009Loss et al ( , 2010aLoss et al ( , 2010b, ao comparar um SPD com rotação entre beringela e milho e um SPC com rotação entre milho e feijão, em Argissolo, relataram maiores teores -no SPD -de matéria orgânica leve (MOL), COT, N do solo, C orgânico particulado (COp), C orgânico associado aos minerais (Coam), e maiores valores de frações húmicas e frações oxidáveis da MOS (graus de oxidação F2, F3 e F4).…”
Section: Introductionunclassified
“…The NT potential to improve carbon contents in tropical and subtropical soils have been reported by other studies (Conceição et al, 2013) [9]. In a vegetable production area of the Brazilian Cerrado, Souza et al (2014) [10] also observed that the use of conservation systems improved the quantity and quality of SOM. However, there is little knowledge about the temporal dynamic of SOM contents in vegetables production areas when conservation systems are adopted, an important question to improve the sustainability of the agricultural soils.…”
mentioning
confidence: 59%
“…These differences were not observed for the total SOC levels ( Table 2). As the F1 fraction comprises the C forms that require the lowest degree of oxidation for extraction (Chan et al, 2001;Souza et al, 2014), our results suggest that the cultivation of these two species may enhance the concentrations of the more labile organic C in the soil. This significant difference in organic C also indicates that the F1 fraction can be used as a sensitive indicator of the changes in soil organic matter due to alterations in the management practices.…”
Section: Oxidizable Organic C Fractionsmentioning
confidence: 84%
“…Thus, the partitioning of soil organic matter into the functional compartments with different dynamics represents an important tool to readily detect recent changes in the soil in response to changes in management practices (Sequeira et al, 2011;Blanco-Moure et al, 2013). The labile fractions of soil organic matter such as LF, POC and C fractions extracted using low degrees of oxidation with H 2 SO 4 (Chan et al, 2001), may be more sensitive indicators of the changes caused by modifications in soil management practices (Loss et al, 2013;Souza et al, 2014;Marques et al, 2015), and an analysis of these compartments will deepen the understanding of SOC dynamics (Carter, 2001). …”
Section: Introductionmentioning
confidence: 99%